Ikaw ay akin - Bernal, Ishmael; Carreon, Jose N.; Lobo, Sergio; Salvador, Augusto; Aunor, Nora; Santos, Vilma; De Leon, Christopher; Romano, Nick; Andolong, Andrea; Zarate, Ernie (Tagalog Ilang-Ilang Productions, 1978)
Rex and Tere have been together for five years. They have a peaceful relationship until Rex met Sandra, a designer. Rex and Tere's relationship became chaotic ; and Rex can't decide whom to choose between the two women.